Pengaruh Adopsi IFRS, Penghindaran Pajak, dan Kepemilikan Manajerial terhadap Manajemen Laba - Ayem, Sri; Ongirwalu, Stella Nenden (Jurnal Ilmiah Akuntansi, 2020)
This study aims to examine the effect of the adoption of International Financial Reporting Standards (IFRS), tax avoidance, and managerial ownership on earnings management. The population in this study is the LQ45 index companies listed on the Indonesia Stock Exchange as many as 15 sample companies during 2014-2018. Data analysis was performed using multiple linear regression techniques. This test uses STATA version 15. The results show that the adoption of International Financial Reporting Standards and managerial ownership has a negative effect on earnings management, while tax avoidance has no effect on earnings management. The results of this study are supported and strengthened by using the Return on Assets control variable which can affect the independent variable on earnings management